2018
DOI: 10.1021/acsami.8b01365
|View full text |Cite
|
Sign up to set email alerts
|

Simple Synthetic Molecular Hydrogels from Self-Assembling Alkylgalactonamides as Scaffold for 3D Neuronal Cell Growth

Abstract: In this work, we demonstrated that the hydrogel obtained from a very simple and single synthetic molecule, N-heptyl-galactonamide was a suitable scaffold for the growth of neuronal cells in 3D. We evidenced by confocal microscopy the presence of the cells into the gel up to a depth of around 200 μm, demonstrating that the latter was permissive to cell growth and enabled a true 3D colonization and organization. It also supported successfully the differentiation of adult human neuronal stem cells (hNSCs) into bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 69 publications
(127 reference statements)
0
58
0
Order By: Relevance
“…Solutions of N-heptyl-ᴅ-galactonamide in dimethylsulfoxide are prepared by dissolving the powder at 2.5 wt% (25 mg/mL) at room temperature with the help of an ultrasound bath. The synthesis of N-heptyl-ᴅ-galactonamide has been described elsewhere 40 or it can be purchased from Innov'Orga, Reims, France. Dimethylsulfoxide has been purchased from Fisher, quality 99 %, non-anhydrous.…”
Section: Gelling Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solutions of N-heptyl-ᴅ-galactonamide in dimethylsulfoxide are prepared by dissolving the powder at 2.5 wt% (25 mg/mL) at room temperature with the help of an ultrasound bath. The synthesis of N-heptyl-ᴅ-galactonamide has been described elsewhere 40 or it can be purchased from Innov'Orga, Reims, France. Dimethylsulfoxide has been purchased from Fisher, quality 99 %, non-anhydrous.…”
Section: Gelling Solutionmentioning
confidence: 99%
“…In our preceding work, we showed that low molecular weight hydrogels of N-alkylglyconamides and more especially, N-heptyl-D-galactonamide (GalC7), are biocompatible and allow the growth and the differentiation of human neural stem cells into neurons and glial cells 40 . For different applications, we were looking for methods that would enable to inject or extrude those gels.…”
Section: Introductionmentioning
confidence: 99%
“…7g). 2 Some of these fibers reach a millimetric length and several microns of width. The sol-gel transition occurs at high temperature, around 65°C, precluding notably the introduction of living matter before setting.…”
Section: Application Of Wet Spinning To N-heptyl-d-galactonamidementioning
confidence: 99%
“…Yet it has been shown that the structure of these fibers at the micrometric/nanometric scale has an impact on the behavior of the cells seeded in these gels. 1,2 Several LMWGs are suitable for cell culture. [3][4][5][6][7][8] Most of them are based on peptides, but other families of LMWGs are also promising for these applications, based on carbohydrates, 2,9-16 nucleosides [17][18][19][20][21][22][23] or other building blocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation